High‐pressure processing of persimmon purée: Stability during chilled storage. Issue 1 (13th November 2019) - Rodriguez, Anabel; Cap, Mariana; Ramos, Nelsi; Godoy, Fernanda; Mascheroni, Rodolfo H.; Vaudagna, Sergio R.
Abstract: The aim of the study was to evaluate the effect of the high pressure (HP) technology on the preservation of persimmon purée during chilled storage (1, 30, and 90 days at 4 ± 1 °C). Results showed that the treatment at 400 MPa for 1 min was enough to eliminate the microbial counts and no regrowth was observed during storage. Physicochemical parameters, phenolic compounds, and antioxidant capacity were not affected by HP and were kept stable during storage. The mechanical and rheological properties were not affected by HP treatments at 500 and 600 MPa, preserving these properties during storage. The HP treatments were not able to effectively preserve the chromatic parameters and achieve the complete inhibition of the enzyme´s activity. The conditions that achieved the best preservation of the quality properties was 600 MPa for 5 min. Practical applications: The sensory and nutritional properties of fruits often determine the consumer choice of food. However, the quality properties of foods can be affected during processing and storage. High pressure (HP) technology has been used in different branches of the food industry. In the present study, the application of HP treatments has demonstrated to be a good alternative to preserve the natural characteristics of fruits, allowing the storage stability of the product for a long time. From this study, criteria for the commercial production of high‐quality persimmon purée with safety requirements could be established.